Modelagem espacial e temporal do balanço hídrico da bacia hidrográfica do açude Epitácio Pessoa - Medeiros , Isabella Carvalho de (2017)
The problem of water scarcity is a reality that has been intensifying all over the world, mainly due to population growth and climatic factors. In Brazil, the semi-arid region is one of the most sensitive to this problem. In Paraíba, the Epitácio Pessoa dam watershed dam, which is of great social and economic importance for the State, is constantly facing problems related to water scarcity. Currently, Epitácio Pessoa dam, responsible for supplying more than 20 municipalities, has only 2,9% of its available capacity. A similar situation has occurred in several other regions in the State. In this regard, the present research aimed to model the water balance of Epitacio Pessoa dam watershed using the SWAT model, in order to contribute to the understanding of the spatial-temporal dynamics of its water balance. For that, the period from 1970 to 1990 was used for the calibration of the model and the period from 1994 to 2014 for the validation, the modeled variable was the flow. The results obtained by the SWAT model were satisfactory, according to the statistical indicators NSE and R², which presented values for Poço de Pedras station, of 0.69 and 0.69, respectively, and for Caraúbas station of 0,64 and 0.65, respectively. These results were higher than the minimum acceptable values (NSE = 0.5 and R² = 0.6), showing that the model was calibrated. Also, the validation of the model presented good results for Poço de Pedras station (NSE = 0.8 and R² = 0.87). However, Caraúbas station results were slightly lower than the desirable (NSE = 0,41 and R² = 0.56). Finally, the values of the water balance components of the watershed were obtained, with annual mean evapotranspiration values of 353.3 mm, surface runoff of 27.34 mm and percolation of 131.53 mm. The simulation of the water balance allowed a greater understanding of the watershed's behavior, showing results consistent with what is expected of a watershed in a semi-arid environment.